2006
DOI: 10.1101/gad.1430406
|View full text |Cite
|
Sign up to set email alerts
|

SUMO modifications control assembly of synaptonemal complex and polycomplex in meiosis of Saccharomyces cerevisiae

Abstract: The synaptonemal complex (SC) is a proteinaceous complex that apparently mediates synapsis between homologous chromosomes during meiotic prophase. In Saccharomyces cerevisiae, the Zip1 protein is the integral component of the SC. In the absence of a DNA double-strand break or the SC initiation protein Zip3, Zip1 proteins aggregate to form a polycomplex (PC). In addition, Zip1 is also responsible for DSB-independent nonhomologous centromere coupling at early meiotic prophase. We report here that Zip3 is a SUMO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
398
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(426 citation statements)
references
References 59 publications
22
398
2
1
Order By: Relevance
“…Although initial attempts failed to detect activity on a variety of standard substrates (e.g., beta-galactosidase, calf histones, bovine serum albumin, human topoisomerase II), SUMO chains were reproducibly generated in an Slx5-and Slx8-dependent manner. This activity has previously been observed using several SUMO E3 ligases [15,19,43]. As shown in Fig.…”
Section: Slx5 and Slx8 Proteins Stimulate Sumo Conjugation Activity Isupporting
confidence: 78%
See 1 more Smart Citation
“…Although initial attempts failed to detect activity on a variety of standard substrates (e.g., beta-galactosidase, calf histones, bovine serum albumin, human topoisomerase II), SUMO chains were reproducibly generated in an Slx5-and Slx8-dependent manner. This activity has previously been observed using several SUMO E3 ligases [15,19,43]. As shown in Fig.…”
Section: Slx5 and Slx8 Proteins Stimulate Sumo Conjugation Activity Isupporting
confidence: 78%
“…Mms21 is conserved in humans [17] and co-purifies with the essential Smc5-Smc6 that is required for recombination-mediated DNA repair [16,18]. Zip3 is a meiotic SUMO E3 ligase with an SPRING domain that plays a role in the formation of the synaptonemal complex [19]. In addition to the SP-RING proteins, human cells contain at least two SUMO E3 ligases, RanBP2 and PC2, that lack any form of RING domain [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…12-15 Although the significance of SUMO-2/3 chains remains uncertain, polymeric Smt3 chains may play a functional role during meiotic chromosomal segregation in yeast. 16 Ub/Ubl proteins are synthesized as precursors, and are processed by proteases to their mature form. These enzymes release residues at the Ub/Ubl C-terminus to expose a conserved Cterminal Gly-Gly motif which is then adenylated in an ATP-dependent process by an E1-activating enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 The functions of sumoylation in higher organisms have been explored in studies on spermatogenesis; it has been shown that sumoylation plays crucial roles in several processes during spermatogenesis, including XY body formation, Figure 1. Subcellular localization of SUMo-1 during mouse oocyte maturation.…”
mentioning
confidence: 99%